2014
DOI: 10.2135/cropsci2013.05.0331
|View full text |Cite
|
Sign up to set email alerts
|

A Non‐thermal Plasma Seed Treatment Method for Management of a Seedborne Fungal Pathogen on Rice Seed

Abstract: Seeds contaminated with pathogens are the primary inoculum for plant diseases in many food crops. Conventional treatments for seedborne diseases use hot water, chlorine or fungicide applications. A novel seed treatment method based on non‐thermal plasma generated by an air dielectric barrier discharge (DBD) device was evaluated in this study as an alternative to these conventional treatments. The non‐thermal plasma at atmospheric pressure and room temperature consisted of partially‐ionized gases that are chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…e germination of many plant species can be improved by NTP treatment. e positive effect of NTP was found on barley (Hordeum vulgare, [49]), maize (Zea mays, [50]), oat (Avena sativa, [51]), rice (Oryza sp., [52]), spinach (Spinacia oleracea L. Beiouzhizun, [53]), bell pepper (Capsicum annuum L. cultivar California Wonder, [54]), and mung bean [55]. On the other hand, the neutral effect was found on oat germination and early growth [43].…”
Section: Seed Germination and Seedling Initial Growthmentioning
confidence: 99%
“…e germination of many plant species can be improved by NTP treatment. e positive effect of NTP was found on barley (Hordeum vulgare, [49]), maize (Zea mays, [50]), oat (Avena sativa, [51]), rice (Oryza sp., [52]), spinach (Spinacia oleracea L. Beiouzhizun, [53]), bell pepper (Capsicum annuum L. cultivar California Wonder, [54]), and mung bean [55]. On the other hand, the neutral effect was found on oat germination and early growth [43].…”
Section: Seed Germination and Seedling Initial Growthmentioning
confidence: 99%
“…This might be a consequence of the removal of pathogenic microbes or activation of the seed germination process by plasma itself (Randeniya and de Groot, 2015). In many studies, plasma treatment demonstrated no adverse effects on seed vitality (such as germination and subsequent growth) at antimicrobial doses (Selcuk et al, 2008;Jo et al, 2014). These results indicate that the plasma treatment is a quite promising technique for seed disinfection.…”
Section: Seed-borne Diseasesmentioning
confidence: 93%
“…Generally, oxygen species is one of the most important materials for sterilization which has been mentioned in many reports on plasma sterilization. Atomic nitrogen radiates at 745 nm and N 2 as the other important reactive particle is detected in the range of 320-400 nm [11,12]. Ultraviolet peaks are at 364.5, 388.5, 388.9, and 397 nm and the peaks of NO are at 296, 357.7, and 378.9 nm [13].…”
Section: Spectroscopy Of G Arc Plasmamentioning
confidence: 99%